Mother Joan of the angels - Iwaszkiewicz, Jarosław 1894-1980; Walaciński, Adam 1928-2015 (Second Run, 2012)
"Set in the 17th century. A convent in a small town is being visited by high-ranking Catholic official trying to exorcise the nun supposedly posessed by demons. A local priest have been burnt for creating this condition by sexual temptation of the nuns, especially the Mother superior who bring on the collective hysteria of the group. There is another young priest who is to help with the exorcism. His first meeting with the convent head, Mother Joanne of the Angels, has her seemingly posessed by Satan - she yells blasphemies and incites the priest. She begs the priest to save her and to help her to be a saint." [filmdienst.de]
Original: Polen 1961
Special features: presented from a new high-definition restoration of the film, supervised by the film's cinematographer Jerzy Wójcik. ; newly filmed, exclusive appreciation by writer and film historian Michael Brooke. ; new and improved English subtitle translation. ; 20-page booklet featuring essays by author and film lecturer Dr David Sorfa, and Michael Brooke on director Kawalerowicz. ; optimal quality dual-layer disc.
Bildformat 1.33:1
Keywords: Film; DVD-Video